Роман Доця Тамари Горіха Зерня: стратегії творення ефекту співпричетності - Гребенюк, Тетяна Володимирівна; Hrebeniuk, T. (My University, 2020)
The article considers narrative strategies of the creation of the effect of the reader’s involvement in the protagonist’s life experience in Tamara Horiha Zernia’s novel Dotsya, which is devoted to the important problem of today — the war on the east of Ukraine. The theoretical framework of the study is based on Monika Fludernik’s cognitive-narratological conception of experientiality referring to the idea of the reader’s familiarization with a character’s experience by narrative means. Three strategies of creating the experientiality in this novel are seen as the most important: mimetism while reflecting the region realities, manipulation by the category of local identity, and vivid emotionality of the novel’s narrative. The protagonist’s depersonalization, the display of corporal reactions and the inclusion of invective digressions into the fictional discourse are considered as prevailing patterns of emotional expression
The novel by tamara horiha zernia dotsya: strategies of creating the effect of cooperation
Keywords: experientiality; narrative strategy; cognitive narratology; mimetism; local identity; patterns of the emotion expression